The Effects of Annealing Parameters on the Crystallization and Morphology of Cu(In,Ga)Se2 Absorber Layers Prepared by Annealing Stacked Metallic Precursors - Chia-Ho Huang; Dong-Cherng Wen (International Journal of Photoenergy)
CIGS films are prepared by single-stage annealing of the solid Se-coated In/Cu-Ga bilayer precursor. The annealing processes were performed using various Ar pressures, heating rates, and soaking times. A higher Ar pressure is needed to fabricate highly crystalline CIGS films, as no extra Se-vapor source is supplied. As the heating rate increases, the surface morphologies of the CIGS films become looser and some cracks are observed. However, the influence of soaking time is insignificant and the selenization process only requires a short time when the precursors are selenized at a higher temperature with a lower heating rate and a higher Ar pressure. In this study, a dense chalcopyrite CIGS film with a thickness of about 1.5-1.6 μm, with large grains (~1.2 μm) and no cracking or peeling is obtained after selenizing at a temperature of 550°C, an Ar pressure of 300 Torr, a heating rate of 60°C/min, and a soaking time of 20 min. By adequate design of the stacked precursor and controlling the annealing parameters, single-stage annealing of the solid Se-coated In/Cu-Ga bilayer precursor is simplified for the fabrication of a fully crystallized chalcopyrite CIGS absorber layers with good crystallization and large grains.